A 5 year review of henoch Schönlein purpura at a tertiary paediatric hospital. (4th April 2011) - Watson, L; Richardson, A R W; Holt, R L; Jones, C; Beresford, M W
Abstract : Aim: To review the incidence of renal involvement and the natural course of Henoch Schönlein Purpura (HSP) over a 5 year period at a tertiary paediatric hospital. Method: Patients were followed-up over a 1 year period, with frequency of visits dependent on proteinuria. At each visit a minimum of blood pressure and urinalysis was performed. Using a standardised data collection pathway all clinical data was collected prospectively. The primary outcome measured was the need for a consultant referral either during or after completing a year of follow-up. Results: 165 patients were identified presenting over 69 months, giving an incidence of 14.5 HSP cases per 100 000 children per year attending our hospital. The mean age at presentation was 7.2 years, with those requiring a renal referral significantly older (9.8± 3.5 vs 6.9±4.0 years; p≤0.01). Non-Caucasian patients were significantly more likely to be referred for renal review (21% vs 6%; p≤0.01). Purpuric rash was a presenting feature in 100% of patients, arthralgaia (45%) and joint swelling (19%) being the next most common presenting features. No patients initially presented with nephrotic or nephritic syndrome. At presentation 14% of patients were hypertensive, no patients had hypertension persisting beyond day 7 of follow-up. 12 (7%) patients from the cohort required referral to a paediatric nephrologist, 3 with raised urine albumin creatinine ratio were referred within 3 months, and the other 9 had persistent proteinuria or haematuria at the end of 12 months. Urine samples performed on day 7 had a negative predictive value of a normal urinalysis indicating a normal outcome of 98%. Conclusion: Older patients and those of non Caucasian ethnicity are at a higher risk of nephritis. Significant nephritis is an infrequent complication of HSP and transient hypertension is common. The follow-up of patients with HSP should be stratified according to urinalysis, blood pressure and renal function.